On the mean square of the periodic zeta-function. II - Černigova, Sondra; Laurinčikas, Antanas (Nonlinear Analysis: Modelling and Control, 2015)
In the paper, the error term in the Atkinson type formula for the periodic zeta-function in the critical strip is considered, and an asymptotic formula for its mean square is obtained. This formula generalizes that proved for the Riemann zeta-function.